Thermal Stability of Polyurethanes from Soybean Oil as Natural Source and its Chemical Modifications - Weimer, Néstor Mariano Santucho (Journal of Research Updates in Polymer Science, 2019)
In this contribution, a summary of recent publications about the thermal stability of polyurethanes from soybean oil as natural source for polyols was made. From the review, it can be concluded that polyurethanes from natural oil-derived polyols decomposed at a temperature up to 30°C higher than petrochemically-based polyurethanes. Chemical modification of soybean oil for polyol synthesis is mainly based on epoxidation. However, we highlighted the possibility of functionalizing soybean oil by maleinization, a route that was very scarcely studied. Maleinization allows the introduction of labile reactive hydrogen to react with isocyanates for polyurethane synthesis with a broad range of properties.